Exploration of University Data Asset Management - Ding, Hongfei; Liu, Qin (Asia Pacific Economic and Management Review, 2025)
With the advent of the digital and big data technology era, data is developing at an unprecedented speed and scale. It has become a consensus that data assets are an important resource for the development of enterprises and institutions. Universities are not only data consumers in the digital economy but also data producers. They generate massive amounts of data in teaching, research, and administrative management. Transforming this data into data assets and managing these new types of assets has become an urgent challenge for university managers. This paper explores the definition and value attributes of university data assets, analyzes the challenges in their management, and proposes corresponding strategies.